Hubungan Terpaan Berita COVID-19 di Televisi dan Tingkat Pendidikan dengan Tingkat Kecemasan Masyarakat dalam Menghadapi Pandemi COVID-19 - Yoga Pratama; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study aims to determine the relationship of each variable, exposure to COVID-19 news on television (X1) and education level (X2) with the level of public anxiety in facing the COVID19 pandemic (Y).This research is a quantitative research with an explanatory type. This study used a nonprobability sampling technique with a total sample of 60 people aged 17-65 years in the city of Semarang who had watched television in the last week. The results of Kendall's Tau correlation test showed that there was no relationship between exposure to COVID-19 news on television and the level of public anxiety as indicated by a significance value of 0.086 (> 0.05). While the level of education has a relationship with the level of public anxiety which is indicated by a significance value of 0.017 (<0.05). The correlation coefficient value is - 0.300, which means that the higher the level of education, the lower the level of public anxiety in facing the COVID-19 pandemic. With these results it is suggested that the next researcher examines other variables in examining the theme of public anxiety levels with more diverse variables such as social demographic factors.